A multinuclear magnetic resonance study of the structures and dynamics of lanthanum(III) complexes in solution. - Chen, Zhigang. (University of Ottawa (Canada), 1993)
The structural and dynamic behaviours of La(III) complexes in solution have been investigated by multinuclear magnetic resonance spectroscopy. In an acetonitrile solution of La(NO$\sb3)\sb3$ 6 H$\sb2$O, a combined $\sp{139}$La and $\sp $O NMR study revealed the existence of the following equilibrium: $\rm \{La(NO\sb3)\sb3(AN)\sb{x}\} + H\sb2O\rightleftharpoons\{La(NO\sb3)\sb3\ H\sb2O(AN)\sb{y}\}$. The NMR results have been quantitatively interpreted through this model. The detailed analysis of $\sp $O NMR spectra of H$\sb2$O allowed the indirect coupling constant between the $\sp $O of the coordinated water and $\sp{139}$La to be estimated. The main focus of the present work was given to the thermodynamic, structural, and dynamic studies of La(III) complexes with crown ethers in non-aqueous solutions. Stable 1:1 cation:crown ether complexes were formed between La(III) and 18C6, B15C5, and 15C5. During the course of the complexation, the crown ethers entered to the first coordination shell of La(III) by replacing the coordinated water and most probably the solvent (AN) molecules. In all the cases, the La(III) cations were coordinated by the oxygen atoms from three bidentate nitrate anions and from the crown ethers. Both cation and ligand exchanges are slow in the system $\rm La(NO\sb3)\sb3$ 6 H$\sb2$O - 18C6 - AN. The rate constant for the exchange is k = 0.15 s$\sp{-1}$ at 333 K. A dissociative exchange mechanism is one of the contributions to the La(III) exchange. This two-site exchange occurs only through a dissociative pathway, which is determined by the structures of the complexes. Since the ligand can not make contact with La(III) from both sides of the complexes, the dissociative mechanism must be the major contribution to the crown ether chemical exchange. An exchange process involving coordinated B15C5 and/or 15C5 was detected by $\sp1$H NMR spectra of the ligands. Detailed $\sp1$H NMR observations were made on the system involving 15C5. A model involving "inner" and "outer" proton exchange was postulated to account for the $\sp1$H NMR experimental data. The structures of La(III) complexes with crown ethers in solution and in the solid state were compared. It might be concluded that the structures of these complexes in solution are very similar to that in the solid state. (Abstract shortened by UMI.)
Keywords: Chemistry, Physical.